2017
DOI: 10.1007/s11894-017-0563-z
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diet in Inflammatory Bowel Disease

Abstract: G&H What is the current understanding of the pathogenesis of inflammatory bowel disease? Does diet play a role?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 42 publications
0
32
0
2
Order By: Relevance
“…Over the last 2 years there has been a significant number of studies referring to adoption of the Med-diet pattern and its associated beneficial outcomes in a plethora of several chronic diseases that are either directly or indirectly related to inflammation. These studies refer to heart failure, CVD [ 25 ], cancer [ 26 , 27 ], obesity [ 28 ], metabolic syndrome [ 29 , 30 , 31 ], diabetes [ 31 , 32 , 33 , 34 ], and other subsequent manifestations such as diabetic retinopathy [ 35 ], asthma [ 36 ], autoimmune diseases such as rheumatoid arthritis [ 37 ], incident frailty risk [ 38 ], non-alcoholic fatty liver disease [ 39 , 40 ], inflammatory bowel disease [ 41 ], cognitive health, the risk of Alzheimer’s disease and dementia [ 42 , 43 , 44 ], and age-related macular degeneration [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 2 years there has been a significant number of studies referring to adoption of the Med-diet pattern and its associated beneficial outcomes in a plethora of several chronic diseases that are either directly or indirectly related to inflammation. These studies refer to heart failure, CVD [ 25 ], cancer [ 26 , 27 ], obesity [ 28 ], metabolic syndrome [ 29 , 30 , 31 ], diabetes [ 31 , 32 , 33 , 34 ], and other subsequent manifestations such as diabetic retinopathy [ 35 ], asthma [ 36 ], autoimmune diseases such as rheumatoid arthritis [ 37 ], incident frailty risk [ 38 ], non-alcoholic fatty liver disease [ 39 , 40 ], inflammatory bowel disease [ 41 ], cognitive health, the risk of Alzheimer’s disease and dementia [ 42 , 43 , 44 ], and age-related macular degeneration [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been done to find an appropriate strategy to control the disease symptoms and inflammation in patients with UC [8]. Patients with UC might take benefit from the consumption of fish oils, polyunsaturated fatty acids, and probiotics [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with UC, a prospective cohort study of 191 patients revealed that high intake of processed and red meat, protein, alcohol, and high sulfur or sulfate increased the likelihood of relapse [ 123 ]. Thus, avoidance of specific food items should be based on individual experience, and no generalized recommendation can be made [ 124 ]. Milk should not be routinely restricted in all patients with inflammatory bowel disease unless patient has severe hypolactasia.…”
Section: The Asian Working Group Guidelines Regarding Diet In Inflammmentioning
confidence: 99%